Framework to precede collaboration in supply chain. Issue 8 (29th November 2018) - Singh, Harjit; Garg, Rajiv Kumar; Sachdeva, Anish
Abstract : Purpose: The purpose of this paper is to help supply chain (SC) decision makers successfully penetrate through SC collaboration and strengthen their SC in the global market by understanding collaborative activities, and understand how these activities are related to each other in the SC. Design/methodology/approach: This paper develops a set of collaborative activities from literature, and the developed model is helpful for SC decision makers to monitor their SC activities and take corrective actions to improve collaboration in their SC by using interpretive structural modeling (ISM) and MICMAC analysis. Findings: This study reveals that collaborative activities increase the value of whole SC. The various activities are modeled on the basis of "an activity influencing other activities" and "an activity influenced by other activities, " which is useful for SC managers to take a decision. Research limitations/implications: The current study is literature based; therefore, there would be need of more explanation of the activities which lead to understand and implement SC collaboration in case of service and manufacturing industry. Practical implications: The model of this study is helpful for decision makers to implement supply chain collaboration (SCC) and to understand various SCC activities on the basis of their driving and dependence power. Originality/value: This research provided insight into skills needed for SC decision makers to implement collaboration in the SC using ISM. The results of the study could be adopted to monitor the existing SCC program or design new collaboration program to meet the global market requirements. To the best of knowledge, there is no reference that discusses SC collaborative activities on the basis of their driving and dependence powers.